THE EFFECT OF BRAND IMAGE AND BRAND TRUST ON CUSTOMER SATISFACTION THROUGH PURCHASING DECISIONS AS AN INTERVENING VARIABLE AT ANCIENT ART SHOP II - Irbad, Yuzky Maulana; Nur Hidayati; Hadi Sunaryo (International Journal of Cultural and Social Science, 2025)
This study aims to analyse the effect of brand image and brand trust on customer satisfaction at Kuno Art Shop II Bali, with purchasing decisions as a mediating variable. The research method used is a quantitative approach with data collection through questionnaires from customers of the store. The population in this study were all Kuno Art Shop II consumers, both local and foreign, with a sample size of 90 respondents. The analytical tool used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through SmartPLS software version 4.0. The results of the analysis show that brand trust has a significant effect on purchasing decisions and indirectly affects customer satisfaction through these decisions. Meanwhile, brand image has a significant effect on purchasing decisions but not directly on customer satisfaction. The purchase decision is shown to have a major influence on customer satisfaction, and the research model shows high predictive power and good variable reliability. The findings confirm the importance of building trust and brand image to improve purchase decisions and customer satisfaction in the antiques and cultural arts industry. The main conclusion highlights that management should focus not only on building image and trust, but also on creating a satisfying purchase experience to increase customer loyalty.